The Method of Calculation of the Evolution of Thermal and Energy Characteristics of the Accelerated Hydration Process of Concrete Products - A. M. Niyakovskii; V. N. Romaniuk; A. N. Chichko; Yu. V. Yatskevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The development of methods for calculating the dynamics of the energy thermal characteristics of the accelerated hydration process is one of the most difficult tasks of heat power engineering. The article describes a new method of calculating the thermal characteristics of the process, focused on its application in the installations of accelerated hydration used for the production of 3D-reinforced concrete structures. The principles of cellular-automatic modeling of energy characteristics of concrete heat treatment process were used in the development of the method. The mathematical apparatus used in the method is based on the finite-difference three-dimensional heat equation, which allows taking into account, due to the system of boundary and initial conditions, the spatial dimensions of the concrete product, the spatial arrangement of the formwork, the spatial distribution of heating elements and other design features of the accelerated hydration system. The input parameters of the models used are the density, thermal conductivity, heat capacity of the concrete mixture and structural elements included in the tooling of the product. Boundary and initial conditions will make it possible to solve modeling problems for any 3D-design. The goal of the study is to develop a method for calculating the energy characteristics dynamics of the hardening of 3D-concrete products subjected to heat treatment, based on a grid non-equilibrium thermal model. The paper presents a mathematical equation apparatus that allows linking the geometric characteristics of the product and the finite-difference equations of thermal conductivity, including sources of heat. A numerical method for determining the energy characteristics of the hardening of 3D-concrete products subjected to heat treatment has been proposed consisting of, depending on the time of heat treatment, the calculation of the outside heat supplied to the concrete product, heat dissipated into the environment, the emitted heat of hydration and the heat accumulated in the concrete product during heat treatment, taking into account the geometry of the product. The method is based on a grid three-dimensional thermophysical model that takes into account the nonequilibrium and the system of boundary conditions that reflect the specifics of the process in the accelerated hydration of concrete. Calculations of the functions of the energy characteristics determining the heat treatment, depending on the time of heat treatment for cubic 3D-concrete products of different sizes have been performed. It is demonstrated that the rate of alteration of energy characteristics can be modeled for products of any spatial configuration.